Optimization of In Vitro Propagation of Curcuma longa Linn. var. Trang 1 - Hansuek, sakulrat; Seephueak, Pornsil; Bootkote, Pitipat (Recent Science and Technology, 2025)
Trang 1 turmeric, commonly known as golden turmeric, is grown extensively in Nakhon Si Thammarat province due to its high live weight of 2.23 tons per rai. It is resistant to bacterial wilt disease and contains an average of 10.62% curcuminoids and 7.99% essential oils, making it quite popular. As a result, output is insufficient to satisfy market demand, and there is a shortage of good-quality plants for cultivation. Therefore, the objective of this study is to propagate the turmeric cv. Trang 1 in vitro to produce large numbers in a short time. Apical shoot induction was studied using bud fragments from turmeric rhizomes. The experimental design was a completely randomized design (CRD). Shoots were surface sterilized and cultured on Murashige and Skoog (MS) with benzyladenine (BA) concentrations of 1, 2, 3, 4, and 5 mg/L for 3 months. It was found that turmeric shoots cultured on MS medium supplemented with 1 mg/L of BA produced the highest number of shoots at 7.60 shoots per explant, shoot height at 6.00 cm, and 4.80 leaves per plant. For root induction, apical shoots were cultured on medium for 3 months. The experimental design was a 7x2 factorial CRD with 2 factors: factor A was naphthylacetic acid (NAA) concentration (0, 0.5, 1, 1.5, 2, 2.5 and 3 mg/L) and factor B was with or without 0.2% of activated charcoal. It was found that MS medium supplemented with 2 mg/L NAA produced the maximum root number at 11.80 roots per plantlet and a root length of 7.40 cm. Turmeric plantlets with healthy roots were transplanted to a nursery in greenhouses with approximately 50% light penetration for one month. The results showed that the turmeric plants had an 80% survival rate and could rapidly grow into vigorous plants.As a result, turmeric propagation by tissue culture is another way to increase the quantity of turmeric plants commercially to obtain large quantities that are consistent and sufficient to meet demand.